SDN Technology and Industry Analysis and Strategy Recommendations for Telecom Operator - Yongbing Fan; Zhilan Huang (Dianxin kexue)
Software defined networking（SDN）proposed a new concept of network design，which emphasized the separation of network control plane and forwarding plane.It made network architecture more open and encourage network innovation.The basic concept and characteristics of SDN were introduced，the SDN core technology and its industry development status were analyzed，the influence of SDN on the future network from the perspective of operators was discussed，and the corresponding application suggestions were given.